ANALYSIS OF SAFETY STOCK SYSTEM IN BUSINESS TRADING (CASE STUDY : UD LEO JAYA) - Leonardo Hanriyanto; Leonaldo Yogi Gunawan; Liem Gai Sin (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this study is to be a model to use the methods of safety stock in business management. This study is very important because the management of safety stocks in Indonesia is still very poor, while many businesses that require this management to keep inventory remain. This research uses UD. Leo Jaya as a case study. This data obtained through direct interview method and analytical data with qualitative technique to find the best model of safety stock system for business management. Keywords : UD Leo Jaya, Safety stock, inventory remain ,direct interview, analytical data